(untitled) (Proceedings of International Interdisciplinary Conference on Sustainable Development Goals (IICSDGs), 2024)
The main objective of this study is to determine the level of implementation and challenges faced by the e-policing project of the Police Investigation Units in Bataan. E-policing project includes e-Blotter or Crime Information Reporting and Analysis System (CIRAS), Case Information Database Management System (CIDMS), e-Subpoena System, e-Rogues Gallery and e-Warrant System. This research employed mixed methods design for gathering and analyzing qualitative and quantitative research and methodologies in a single study. For the quantitative part, 65 personnel assigned to the components of the e-policing project were involved. Meanwhile, the 15 participants for the qualitative portion of the study were chosen from the respondents. The findings of the study revealed that the level of implementation of the e-policing project is “Fully Implemented”. However, results of qualitative investigations revealed the following challenges in the implementation of e-policing project: slow internet connection, untrained personnel in e-policing, bogging down of the system, and inaccessibility due to the volume of users. The study concludes that the widespread adoption of e-policing system underscores the need for skills and trainings in the delivery quality services for public safety and law enforcement agencies effectiveness. However, privacy and security issues must be carefully taken into account to make sure that these technologies are used in a way that fosters citizen confidence and openness. Additionally, it suggests the necessity of providing ongoing training to police personnel involved in e-policing to keep them updated. To facilitate efficient e-policing, it proposes the installation of high-speed Internet connections in police workplaces.